2003
DOI: 10.1046/j.1538-7836.2003.00182.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of plasminogen in angiogenesis in vivo

Abstract: Summary. Plasminogen, by virtue of its role in the degradation of extracellular matrix proteins and by facilitation of cell migration, may contribute to angiogenesis. Objective: the purpose of this study was to evaluate the contribution of plasminogen to angiogenesis in vivo. Methods: Angiogenesis was assessed in gene-targeted mice with de®ciencies of plasminogen, urokinase plasminogen activator (uPA), and urokinase receptor (uPAR) in a mouse corneal model. In wild-type mice, female and young mice showed a tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 43 publications
4
42
0
2
Order By: Relevance
“…Within ischemic tissues, we found VEGF-A staining mainly in CD11b ϩ cell by immunohistochemistry ( Figure 4C). VEGF-A administration partially rescued impaired angiogenesis observed in Plg Ϫ/Ϫ HL ischemic mice, as reported, 34 but did not in MMP-9 Ϫ/Ϫ mice ( Figure 4D-H).…”
Section: Inhibition Of Vegf-a Signaling Prevents Tpa-mediated Cell Mosupporting
confidence: 85%
“…Within ischemic tissues, we found VEGF-A staining mainly in CD11b ϩ cell by immunohistochemistry ( Figure 4C). VEGF-A administration partially rescued impaired angiogenesis observed in Plg Ϫ/Ϫ HL ischemic mice, as reported, 34 but did not in MMP-9 Ϫ/Ϫ mice ( Figure 4D-H).…”
Section: Inhibition Of Vegf-a Signaling Prevents Tpa-mediated Cell Mosupporting
confidence: 85%
“…27 The release of the antiangiogenic HRR/PRR fragment from HRG may therefore act to perturb proangiogenic effects associated with activated plasminogen. 46 A gene knock-out study in mice has shown that plasminogen promotes vascular remodeling via both fibrinogendependent and -independent mechanisms. 47 It is also plausible that by reducing the levels of intact HRG, the ability of the full-length protein to promote angiogenesis through its interaction with thrombospondin will For personal use only.…”
Section: Discussionmentioning
confidence: 99%
“…Mice deficient in plasminogen develop normal blood vessels, but are disturbed in VEGF-induced and bFGF-induced angiogenesis in the cornea; data on u-PA-deficient animals are unequivocal. 112,113 Neovascularization after myocardial infarction depends equally on u-PA/plasmin activities as on MMPs. 42 However, one cannot discriminate on the basis of the data available whether the u-PA/plasmin contribution acts largely via endothelial cells on angiogenesis or that the invasion of leukocytes and endothelial progenitor cells, which may supply additional growth factors, also contributes to this effect.…”
Section: The Upar-integrin Complexmentioning
confidence: 99%